(3GdbjGOI GdEOGQjIs - (3eMeO YHO GdebUhO(B, (3eMeOs ((3YeGf(B:s (3ecJHI GdeLJeY GdYQHj(B,s, 2006)
(3Gdeaghe GdYGe ddbjGOI GdEOGQjI(B- (3fXQI JGQjNjI aj af GdEOGQI(B- (3JhLjgGJ GdbjGOI hGdQbGHI GdEOGQjI(B- (3egGQGJ GdbjGOI GdEOGQjI(B- (3hXGFa GdEOGQI(B.s
Keywords: (3GdEOGQIs; (3GdbjGOIs; (3GdbjGOI GdEOGQjIs